A child with nephrotic syndrome in the relapse period – a preventive and therapeutic role of a nurse - Rogowska, Marta (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Nephrotic syndrome is a kidney disease that is a complex of biochemical and clinical symptoms. The diagnosis of a child with nephrotic syndrome is confirmed by proteinuria exceeding 50mg / kg body weight / day, occurrence of edema and hypertension. Thenephrotic syndrome of the majority occurs with periods of exacerbation and remission. Treatment is carried out using the standard steroid therapy method. Aim The aim of the study is to present the preventive and therapeutic role of a nurse over a child with nephrotic syndrome during relapse. Overview The conclusions indicate that the child with nephrotic syndrome in the relapse period requires proper treatment of medical personnel, where the nurse plays a big role in the treatment process. When solving most of the care problems, help from the child’s parents is necessary. The child has all the characteristic symptoms associated with nephrotic syndrome. Taking care of a child is a crucial point during the healing process, since it is the time of observation, which enables noticing all symtoms or malfunctions appearing and, having done that, reacting fast by starting the healing process. It is also crucial to monitor patient’s fluid levels’ balance and measure blood pressure. Conclusion In the care of a child with nephrotic syndrome, the preventive and therapeutic role of the nurse is extremely important to avoid the recurrence of the disease.